Islamic-based anti-corruption education to build integrity zones among ma'had al-jami'ah students at uin Maulana Malik Ibrahim Malang - Gufron Gufron; Dewi Chamidah; M. Anwar Firdausy; Inayatur Rosyidah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This research aims to analyze the implementation of anti-corruption education at Ma'had al-Jami'ah UIN Maliki Malang. This research includes field research, which is included in the type of qualitative research using descriptive methods. Data collection techniques in this research include documentation review, observation, and interviews. The number of samples used in this research was 100. Qualitative data analysis techniques use three-step data analysis technique theory, namely condensing data, presenting data, and drawing conclusions or verification. The research results show that the anti-corruption education center at Ma'had al-Jami'ah UIN Maliki Malang implemented the insertion of relevant learning material. Apart from that, ma'had culture is an important instrument for building students' clean character and integrity. Positioning the integrative-inclusive anti-corruption education model based on Qami' al-Thughyan's book material more applicatively as a learning approach.